Physiological and technical demands of 4 v 4 games in elite youth soccer players - Jones, S.; Drust, B. (Kinesiology, 2007)
Eight elite male soccer players from a Premier League Soccer Academy completed 4 v 4 and 8 v 8 games. The physiological responses to match-play were determined for each player by recording their heart rates during all the games and filming each player to determine individual work-rate profiles and evaluate technical actions. Mean ± SD heart rate for 4 v 4 and 8 v 8 matches were not significantly different (4 v 4, 175 ± 10 beats/min; 8 v 8, 168 ± 6 beats/min). Total distance covered during games was also similar (4 v 4, 778 ± 160 m; 8 v 8, 693 ± 103; P>0.05). The total distance covered by walking, jogging and sprinting did not significantly differ with the number of players included in the game. Significant differences were not-ed for utility (backward and sideways) movements (P<0.05) with greater distances covered in 4 v 4 (140 ± 68 m) than 8 v 8 (107 ± 51 m) games. Reductions in the number of players significantly (P<0.05) increased the number of individual ball contacts per game from 13 ± 7 in 8 v 8 to 36 ± 12 in 4 v 4. The data from this investigation suggest that the number of players involved does not seem to be a crucial determinant in the demands of match-play. This observation is in contrast to more technically related actions that are significantly influenced by player number.